2021
DOI: 10.3390/cancers13123074
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Discontinuation in Metastatic Melanoma: Lessons from Real-Life Clinical Experience

Abstract: Background: Immunotherapy has revolutionized outcomes for melanoma patients, by significantly prolonging survival and probably even curing a fraction of metastatic patients. In daily practice, treatment for responding patients is often discontinued due to treatment-limiting toxicity, or electively, following a major tumor response. To date, the criteria for a safe stop and the optimal duration of treatment remain unclear. Patients and methods: This is a real-world single-site cohort of 106 advanced melanoma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
(57 reference statements)
2
20
0
Order By: Relevance
“…Asher et al . described 19 (24%) relapses among 80 patients who achieved a CR 6 . These studies and our results indicate that, in the real world, 80–90% of patients who achieved a CR had good outcomes even if the treatment had been discontinued.…”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…Asher et al . described 19 (24%) relapses among 80 patients who achieved a CR 6 . These studies and our results indicate that, in the real world, 80–90% of patients who achieved a CR had good outcomes even if the treatment had been discontinued.…”
Section: Figuresupporting
confidence: 71%
“…Dear Editor , It is not known how long anti‐programmed death‐1 (anti‐PD‐1) therapy should be continued for patients with melanoma who have achieved a good response. Only a few studies have investigated this topic, and most did not include acral or mucosal melanomas 1–6 . We retrospectively analysed 57 patients with advanced melanoma (including 12 patients with unresectable lymph node involvement) treated with anti‐PD‐1 monotherapy who achieved a complete response (CR) from 16 collaborating institutions treated during the period from 1 September 2014 to 31 July 2019.…”
Section: Figurementioning
confidence: 99%
“…Hence, long-term use of ICIs, as needed for the treatment of ADPKD, is likely not translatable. However, several cancer studies suggest a durable response and progression-free survival after discontinuation of mono-or combination ICI therapy for 6-12 months depending on the type of cancer (68)(69)(70). The underlying mechanisms associated with this treatment-free survival remain unclear but likely correspond to a permanent remodeling of the TME associated with innate and adaptive immune memory.…”
Section: Discussionmentioning
confidence: 99%
“…In a single cohort study examining patients with advanced melanoma treated with anti-PD-1 monotherapy of nivo + ipi, multivariate analysis revealed that patients with a non-CR to treatment as best overall response (BOR) and in cases where immunotherapy was given in the advanced line (where previous lines of treatment included ipilimumab monotherapy, targeted therapy, prior pembrolizumab, or nivo + ipi) should be treated for longer periods of time, with elective discontinuation discouraged prior to the 18-month timepoint ( 48 ). Finally, in another study examining CR in patients following anti-PD-1 treatments, 102 patients stopped treatment after a CR after a median duration of 9.4 months.…”
Section: Long-term Outcomes To Icbmentioning
confidence: 99%